DishZle / Aiza Johari … [et al.] - Johari, Aiza; Morni, Affidah; Awang Shuib, Awang Rozaimie; Sahari, Siti Huzaimah; Kamri, Thalany (Universiti Teknologi MARA, 2018)
Teaching students to learn new vocabularies and sequencing of ideas can be challenging to many students as they might find such tasks to be challenging boring. Thus, interactive teaching materials are necessary in grabbing learners’ attention span and interests, and in enhancing their involvement. DishZle is a self-designed 2-in-1 language game which makes learning English be more interactive and exciting with its colourful pictures. It also engages the players’ involvements via team play and cooperation. The theme of this game focuses on various traditional dishes in Malaysia. Students who play this game can enhance their pre-existing knowledge of local dishes, learn new words (local dishes and ingredients) and improve their sequencing skills by using linkers. The game is suitable for beginner to intermediate learners of English in any ESL classrooms (as pre or post activities). To add, DishZle can also be introduced to foreign tourists who wish to know more about our local dishes. Travel agencies and hospitality services can offer enjoyable and rewarding activities for the tourists by displaying this game at tourism spots, hotels, homestays or holiday resorts. As the matter of fact, tourists can even purchase the game as souvenirs. The novelties of the game are it involves pictorial illustrations of famous yet authentic local dishes and the ingredients through magnetic board and its pieces, and jumbled arrangements of dish preparations in the form of flip charts. This game can be used in ESL classroom as it enhances fun learning, communicative competency, team work and cooperation as well as develops English language components